MANAJEMEN STRATEGIS PENANGGULANGAN KEMISKINAN DI KOTA SURAKARTA - Wijayanti, Sumilir (JI@P, 2017)
Surakarta development policy has a priority in poverty reduction as the elaboration in Vision Mission Mayor and Deputy Mayor. The poverty rate Surakarta in 2010 amounted to 14.99%. Performance targets set in 2015 by 10% with realization amounted to 10.97%. The performance targets set for poverty reduction RPJMD Surakarta 2016-2021 City at 7.5%. This is the underlying authors conducted a study analysis of strategic management for poverty reduction in Surakarta covering (strategy formulation, strategy implementation and assessment strategies) to describe poverty in Surakarta and what might be causing long-term targets are set is not reached. The study authors conducted a qualitative study with research sites in the Secretariat TKPKD Surakarta and Village (Gajahan, Serengan, Pajang, Sumber and Kepatihan Wetan). The poverty problem in Surakarta identified include issues (health, education, employment, food security and basic welfare infrastructure). The findings of the study of strategic management for poverty reduction in Surakarta, that : (1) in the formulation of the strategy, there are three factors that need attention : a. factor analysis of the external environment in order of priority on social issues, population and environment, b. factor internal analysis in order to focus on CSR’s participation in the allocation of resources, c. The annual target-setting by the functional division can be selected as the basis for their next strategy. (2) in the implementation of the strategy there are two factors, that : a. integration of the functional division pattern is not clearly visible, is still partial and sectorial, for it needs to develop a correlation with a focus target poor people in the village with the highest poverty pockets, b. providing access to information and education to the poor, the development of innovation to be equipped with operational support, and the need to build an integrated system as well as providing space for public participation. (3) in the assessment of the strategy, there are two factors that : a. need consistency that the target of achieving long-term has not translated into the realization of the annual target of a functional division implementing poverty reduction programs, b. to be reviewed the appropriateness and feasibility beneficiaries of poverty alleviation programs associated with the administration of residence, and c. dalah potential competitive advantage and the vocational culture can be developed as a solution to poverty reduction. Keywords : Strategy, Formulation, Implementation, Assessment Strategies and Achieving Performance